Interpretation of anatomic correlates of outer retinal bands in optical coherence tomography. Issue 20 (October 2021) - Yao, Xincheng; Son, Taeyoon; Kim, Tae-Hoon; Le, David
By providing the sectioning capability to differentiate individual retinal layers, optical coherence tomography (OCT) is revolutionizing eye disease diagnosis and treatment evaluation. A better understanding of the hyper- and hypo-reflective bands in retinal OCT is essential for accurate interpretation of clinical outcomes. In this article, we summarize the interpretations of clinical OCT and adaptive optics (AO) OCT (AO-OCT) of the outer retina in the human eye, and briefly review OCT investigation of the outer retina in animal models. Quantitative analysis of outer retinal OCT bands is compared to established parameters of retinal histology. The literature review and comparative analysis support that both inner/outer segment (IS/OS) junction and IS ellipsoid zone nonexclusively contribute to the second band; and OS, OS tips, and retinal pigment epithelium apical processes contribute to the third band in conventional OCT. In contrast, AO-OCT might predominantly detect the IS/OS junction and OS tip signals at the second and third bands due to its improved sectioning capability and possible AO effect on the sensitivities for recording ballistic and diffusive photons from different regions of the outer retina.